The periodic topography of ice stream beds : insights from the Fourier spectra of mega-scale glacial lineations - Spagnolo, Matteo; Bartholomaus, Timothy C.; Clark, Chris D.; Stokes, Chris R.; Atkinson, Nigel; Dowdeswell, Julian A.; Ely, Jeremy C.; Graham, Ali G. C.; Hogan, Kelly A.; King, Edward C.; Larter, Robert D.; Livingstone, Stephen J.; et al. (Journal of Geophysical Research: Earth Surface, 2017)
The research was funded by the NE/J004766/1 UK NERC New Investigator and a SAGES PECRE grants awarded to MS. The Amundsen Sea Embayment multi-beam data were acquired on cruise JR141 of the RRS James Clark Ross in 2006 (PI: R. Larter, British Antarctic Survey). The Pine Island multi-beam data were acquired on cruise OSO0910 (Chief scientists: J. Anderson, Rice University, and M. Jakobsson, Stockholm University). The Marguerite Trough multi-beam data were acquired on cruises JR59, JR71, JR157 and NBP0201. This research would not have been possible without the hard work of scientists and crew during these research cruises. John Anderson and Martin Jakobsson are thanked for providing easy access to the Pine Island bathymetries. We would like to thank John Shaw, Roger Hooke, an anonymous reviewer and the Editor, Bryn Hubbard, for their constructive comments and suggestions that have greatly improved the original manuscript. Underlying bathymetric/topographic data are available by request to the PI/chief scientists of the respective cruises/LIDAR acquisition programs. The spectral results can be accessed by request to T. C. Bartholomaus (tbartholomaus@uidaho.edu) or M. Spagnolo (m.spagnolo@abdn.ac.uk). Peer reviewed